2013
DOI: 10.4292/wjgpt.v4.i2.23
|View full text |Cite
|
Sign up to set email alerts
|

Standard triple versus levofloxacin based regimen for eradication ofHelicobacter pylori

Abstract: AIM:To compare the eradication rates for Helicobacter pylori (H. pylori ) and ulcer recurrence of standard triple therapy (STT) and levofloxacin based therapy (LBT). METHODS:Seventy-four patients with perforated duodenal ulcer treated with simple closure and found to be H. pylori infected on 3 mo follow up were randomized to receive either the STT group comprising of amoxicillin 1 g bid , clarithromycin 500 mg bid and omeprazole 20 mg bid or the LBT group comprising of amoxicillin 1 g bid , levofloxacin 500 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Comparable results have been reported in study by Gopal et al and another study by Cheng H et al who compared the standard clarithromycin triple therapy to levofloxacin-contained triple therapy with eradication rates lower than our results [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…Comparable results have been reported in study by Gopal et al and another study by Cheng H et al who compared the standard clarithromycin triple therapy to levofloxacin-contained triple therapy with eradication rates lower than our results [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…Earlier reports from this institute showed a prevalence of H. pylori infection in perforated duodenal ulcer ranging from 56% to 65%. [ 5 15 16 ] H. pylori prevalance in the present study was 64.76%. In the present study, ST achieved an eradication of 71.43%, 78.13%, and 86.20% by ITT, mITT, and PP analyses, respectively.…”
Section: Discussionsupporting
confidence: 42%
“…Recent meta-analysis from 104 studies in South Korea comprising 42,124 patients found the overall cure rate for triple therapy was 74.6% (95% CI 72.1%–77.2%) by intention-to-treat (ITT) and 82.0% (95% CI, 80.8%–83.2%) by per-protocol (PP), and the cure rate was decreased significantly from 1998 to 2013 [ 69 ]. Several studies in West and South Asia also showed the ineffectiveness of triple therapy as a first line treatment [ 32 , 70 ]. Moreover, substitution with MNZ in Vietnam still showed similar results with a cure rate <70% [ 71 ].…”
Section: The Various Established Eradication Regimens In Asiamentioning
confidence: 99%